Rheumatic chorea as the first presenting sign in a 12-year-old male child - Patel, Bhargav G. (International Journal of Contemporary Pediatrics, 2025)
Rheumatic chorea (RC) is a movement disorder seen in young children and adolescents with a recent history of incompletely treated group A beta-haemolytic streptococcal (GABHS) pharyngitis. Although, it rarely presents as the first manifestation of the disease, physicians should be aware of the disease, so that early diagnosis and prompt treatment may lead to elimination of the pathogen and prevent further disease progression. We present a case of a 12 years old male child who presented with only RC as the first clinical sign.